2021
DOI: 10.3390/ijms222111456
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of MEHP Inhibitory Action and Analysis of Potential Replacement Plasticizers on Leydig Cell Steroidogenesis

Abstract: Steroid production in Leydig cells is stimulated mainly by the pituitary luteinizing hormone, which leads to increased expression of genes involved in steroidogenesis, including the gene encoding the steroidogenic acute regulatory (STAR) protein. Mono(2-ethylhexyl)phthalate (MEHP), the active metabolite of the widely used plasticizer DEHP, is known to disrupt Leydig steroidogenesis but its mechanisms of action remain poorly understood. We found that MEHP caused a significant reduction in hormone-induced steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…The OC mixture was designed to approximate levels of organochlorines found in Arctic ringed seal blubber [ 39 ], a main diet constituent of the Inuit population in Northern Québec, Canada. The pure mixture of organochlorines (15 components in total) was diluted in dimethylsulfoxyde (DMSO) purchased from Sigma-Aldrich Canada (Oakville, ON, Canada) as described previously [ 17 , 18 , 22 , 39 ] to obtain the proportions listed in Table 1 . This organochlorine mixture was used in whole animal studies and found to disrupt reproductive development and function in male rats over several generations [ 22 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The OC mixture was designed to approximate levels of organochlorines found in Arctic ringed seal blubber [ 39 ], a main diet constituent of the Inuit population in Northern Québec, Canada. The pure mixture of organochlorines (15 components in total) was diluted in dimethylsulfoxyde (DMSO) purchased from Sigma-Aldrich Canada (Oakville, ON, Canada) as described previously [ 17 , 18 , 22 , 39 ] to obtain the proportions listed in Table 1 . This organochlorine mixture was used in whole animal studies and found to disrupt reproductive development and function in male rats over several generations [ 22 , 33 , 34 , 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…ELISAs for progesterone quantification were performed as recommended by the manufacturer (Cayman Chemical, Ann Arbor, MI, USA) as described previously [ 17 , 18 , 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Penicillin and streptomycin sulphate were added to the cell culture media to a final concentration of 50 mg/L, and all cell lines were kept at 37 °C, 5% CO 2 in a humidified incubator. All cell lines were validated by morphology and Leydig cell lines by quantifying steroidogenic output (progesterone for MA-10) as previously described [ 25 , 27 , 39 , 73 , 74 , 75 , 76 , 77 ]. MA-10 (60,000 cells per well) and CV-1 (25,000 cells per well) were transiently transfected using polyethylenimine hydrochloride (PEI) (Sigma-Aldrich Canada, Oakville, ON, Canada) as previously described [ 39 , 78 ] or the calcium phosphate co-precipitation method as described in [ 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…MEHP decreases the production of StAR protein and leads to a reduction in cholesterol transport. Apart from inducing oxidative stress in Leydig cells, exposure to a high level of MEHP inhibits the activities of steroidogenic enzymes such as 3β and 17β hydroxysteroid dehydrogenases, thereby altering testosterone biosynthesis [31,32]. MEHP affects spermatogenesis by decreasing the number of Sertoli cells and its interaction with gonocytes and triggers testicular apoptosis by increasing Fas ligand expression [33 -35].…”
Section: Mechanism Of Action Of Endocrine Disruptors On the Male Repr...mentioning
confidence: 99%